Green Hydrogen—Production and Storage Methods: Current Status and Future Directions - Ana-Maria Chirosca; Eugen Rusu; Viorel Minzu (Energies)
Green hydrogen has become a central topic in discussions about the global energy transition, seen as a promising solution for decarbonizing economies and meeting climate goals. As part of the process of decarbonization, green hydrogen can replace fossil fuels currently in use, helping to reduce emissions in sectors vital to the global economy, such as industry and transport, as well as in the power and heat sectors. Whilst there is significant potential for green hydrogen, there are also challenges. The upfront costs for infrastructure and technology are high, and the availability and accessibility of the renewables needed for production varies by region. Green hydrogen production and storage technologies are continuously evolving and being promoted as the demand for hydrogen in many applications grows. Considering this, this paper presents the main methods for its production and storage, as well as its economic impact. Hence, the trend of governments and international organizations is to invest in research and development to make this technology more accessible and efficient, given the carbon reduction targets.